Predicting 6-minute walking test outcomes in patients with chronic obstructive pulmonary disease without physical performance measures. (October 2022) - Romero, Daniel; Blanco-Almazán, Dolores; Groenendaal, Willemijn; Lijnen, Lien; Smeets, Christophe; Ruttens, David; Catthoor, Francky; Jané, Raimon
Highlights: Adding cardiopulmonary markers to physical parameters improve classical 6MWD models in COPD. No walking exercise is needed to estimate 6MWT outcomes using Bayesian networks. Disease severity in COPD can be inferred based on actual patient's 6MWT outcomes. Personalized models of disease progression may help to reduce hospitalization and mortality in COPD. Abstract: Background and Objective: Chronic obstructive pulmonary disease (COPD) requires a multifactorial assessment, evaluating the airflow limitation and symptoms of the patients. The 6-min walk test (6MWT) is commonly used to evaluate the functional exercise capacity in these patients. This study aims to propose a novel predictive model of the major 6MWT outcomes for COPD assessment, without physical performance measurements. Methods: Cardiopulmonary and clinical parameters were obtained from fifty COPD patients. These parameters were used as inputs of a Bayesian network (BN), which integrated three multivariate models including the 6-min walking distance (6MWD), the maximum HR (HRmax ) after the walking, and the HR decay 3 min after (HRR3 ). The use of BN allows the assessment of the patients' status by predicting the 6MWT outcomes, but also inferring disease severity parameters based on actual patient's 6MWT outcomes. Results: Firstly, the correlation obtained between the estimated and actual 6MWT measures was strong ( R  = 0.84, MAPE = 8.10% for HRmax ) and moderate ( R  = 0.58, MAPE = 15.43% for 6MWD and R  = 0.58, MAPE = 32.49% for HRR3 ), improving the classical methods to estimate 6MWD. Secondly, the classification of disease severity showed an accuracy of 78.3% using three severity groups, which increased up to 84.4% for two defined severity groups. Conclusions: We propose a powerful two-way assessment tool for COPD patients, capable of predicting 6MWT outcomes without the need for an actual walking exercise. This model-based tool opens the way to implement a continuous monitoring system for COPD patients at home and to provide more personalized care.